2018
DOI: 10.33549/physiolres.933670
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling in IgA Nephropathy and Focal and Segmental Glomerulosclerosis

Abstract: The aim of the study was to characterize by molecular profiling two glomerular diseases: IgA nephropathy (IgAN) and focal segmental glomerulosclerosis (FSGS) and to identify potential molecular markers of IgAN and FSGS progression. The expressions of 90 immune-related genes were compared in biopsies of patients with IgAN (n=33), FSGS (n=17) and in controls (n=11) using RT-qPCR. To identify markers of disease progression, gene expression was compared between progressors and non-progressors in 1 year follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In adult-onset minimal change disease, levels of VCAM and E-selectin were increased and associated with severity of nephrotic syndrome [146]. A multicenter study revealed that IgAN and focal segmental glomerulosclerosis (FSGS) had higher levels of P-selectin than healthy controls [147]. However, in CKD patients with atrial fibrillation, levels of P-selectin and E-selectin did not correlate with eGFR [148].…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%
“…In adult-onset minimal change disease, levels of VCAM and E-selectin were increased and associated with severity of nephrotic syndrome [146]. A multicenter study revealed that IgAN and focal segmental glomerulosclerosis (FSGS) had higher levels of P-selectin than healthy controls [147]. However, in CKD patients with atrial fibrillation, levels of P-selectin and E-selectin did not correlate with eGFR [148].…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%
“…To fully explain kidney damage in IgAN, it is necessary to fully understand the effects of TLR4 in the development of glomerulopathy, involving both glomerular cells and circulating leukocytes. Studies have shown that the administration of LPS activates TLR4 receptors on mesangial cells, and causes the release of chemokines (CXCs), which promotes neutrophil infusion and the development of glomerulonephritis [114][115][116]. In addition, the IFN-γ and IFN-α responses induced by TLR activation induce overexpression of the B-cell activation factor (BAFF) in dendritic cells, favoring the expansion of B-cells and increasing IgA synthesis [117][118][119][120][121].…”
Section: Iga Nephropathy (Igan)mentioning
confidence: 99%
“…We demonstrated association of the progresson of IgAN with polymorphisms of the ET-1 gene [97]. Association of ET-1 expression with the progression of IgAN was also confirmed using molecular profiling [98]. A specific ET-receptor antagonist (FR 139317) was shown to suppress the development of histologic lesions and proteinuria in ddY mice with IgAN [99].…”
Section: Conflicts Of Interestmentioning
confidence: 86%